Analisis Hambatan yang Dihadapi Guru IPA Dalam Mengimplementasikan Kurikulum 2013 di Sekolah Swasta Kota Makassar - Haris Munandar (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The purpose of this study is "To analyze the obstacles faced by science teachers in implementing the 2013 curriculum in private schools in Makassar. Data collection techniques are carried out by: (1) distribution of questionnaires, (2) interviews, (3) documentation, how to collect samples by purposive sampling techniques. While the data analysis technique used is qualitative descriptive analysis.The results showed that from the three schools where the research was located with reference to three aspects including aspects of learning planning, aspects of learning implementation, and aspects of learning evaluation, an average score of 9.75 was obtained on the planning aspect which showed the highest obstacles in the indicator of understanding and compiling the syllabus structure in the 2013 curriculum which was included in the category of many obstacles, while the lowest obstacle in the indicator determined the learning method that falls into the category of very few obstacles. This means that in this aspect of planning, teachers experience quite a lot of obstacles. In the aspect of learning implementation, the same score was obtained, which was an average of 9.75 which showed the highest obstacle on the indicator of understanding of the basic concepts of the scientific approach which was included in the category of many obstacles, while the lowest obstacle on the indicator of carrying out preliminary activities with a scientific approach, and the application of 5M in the learning process according to the scientific approach which was included in the category of very few obstacles. This means that in this aspect there are also quite a lot of obstacles, while for the learning evaluation aspect, there is a slight increase in score, which is an average of 12.77. There is an increase in scores in the aspect of learning evaluation because generally teachers still experience many obstacles in understanding the concept of authentic assessment, processing and presenting grades in the form of report cards, and conducting assessments through the realm of attitudes. This means that in this aspect of evaluation, science teachers also experience quite a lot of obstacles in implementing the 2013 curriculum.